2021
DOI: 10.1002/pon.5805
|View full text |Cite
|
Sign up to set email alerts
|

Mortality from cancer in people with severe mental disorders in Emilia Romagna Region, Italy

Abstract: Objective: To examine cancer-related mortality in patients with severe mental disorders (SMI) in the Emilia Romagna (ER) Region, Northern Italy, during the period 2008-2017 and compare it with the regional population. Methods:We used the ER Regional Mental Health Registry identifying all patients aged ≥18 years who had received an ICD-9CM system diagnosis of SMI (i.e., schizophrenia or other functional psychosis, mania, or bipolar affective disorders) during a 10-year period (2008)(2009)(2010)(2011)(2012)(2013… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Mortality in patients with SMI, especially those affected by schizophrenia and schizophrenic spectrum disorders, has been the object of several studies which indicated a higher mortality rate in patients with SMI and cancer in several countries 35 . In this issue, these data were confirmed by the only research submitted on this topic, a 10‐year follow‐up study of almost 3000 patients with schizophrenia and bipolar spectrum disorders who died from cancer in Northern Italy 36 . The authors found a higher mortality rate (50% higher) for cancer in patients with SMI with respect to the general population and a higher proportion of deaths in the younger age class among patients with SMI than among the general population.…”
Section: Overview Of the Special Issue Contentmentioning
confidence: 77%
See 1 more Smart Citation
“…Mortality in patients with SMI, especially those affected by schizophrenia and schizophrenic spectrum disorders, has been the object of several studies which indicated a higher mortality rate in patients with SMI and cancer in several countries 35 . In this issue, these data were confirmed by the only research submitted on this topic, a 10‐year follow‐up study of almost 3000 patients with schizophrenia and bipolar spectrum disorders who died from cancer in Northern Italy 36 . The authors found a higher mortality rate (50% higher) for cancer in patients with SMI with respect to the general population and a higher proportion of deaths in the younger age class among patients with SMI than among the general population.…”
Section: Overview Of the Special Issue Contentmentioning
confidence: 77%
“…35 In this issue, these data were confirmed by the only research submitted on this topic, a 10-year follow-up study of almost 3000 patients with schizophrenia and bipolar spectrum disorders who died from cancer in Northern Italy. 36 The authors found a higher mortality rate (50% higher) for cancer in patients with SMI with respect to the general population and a higher proportion of deaths in the younger age class among patients with SMI than among the general population.…”
Section: Cancer Mortalitymentioning
confidence: 91%
“…Research carried out in one Australian state for different cancer sites showed similar results, with a higher proportion of cancer with metastases at diagnosis, a reduced likelihood of surgery and radiotherapy, and fewer chemotherapy sessions overall among the population with SMI [ 11 ]. Despite a relative consistency in these first findings, there is still a dearth of research resorting to linked data between community and hospital care to comprehensively document cancer care pathways for people with SMI in different national settings, using large sample sizes, consensual indicators of care quality within the context of clinical guidelines, and a control group, as recently advocated [ 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cancer is one of the leading causes of death in people with mental disorders 1,2 . Although cancer incidence rates in those with a mental illness are equal to, or lower than, in those without a mental disorder, 3,4 cancer mortality rates in people with mental disorders are high 2,5–9 . Previous reports have shown that people with a severe mental illness are more likely to have delayed cancer detection and less likely to receive standard treatments for cancer than those without a severe mental illness 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Although cancer incidence rates in those with a mental illness are equal to, or lower than, in those without a mental disorder, 3,4 cancer mortality rates in people with mental disorders are high. 2,[5][6][7][8][9] Previous reports have shown that people with a severe mental illness are more likely to have delayed cancer detection and less likely to receive standard treatments for cancer than those without a severe mental illness. 10,11 Moreover, other reports have shown that people with schizophrenia receive less palliative care and fewer opioid prescriptions.…”
Section: Introductionmentioning
confidence: 99%